Wanted: Challenging Design Ideas for Ageing. (March 2014) - Wilkinson, Katherine; Farrelly, Lorraine
Abstract In 2012‐13, the Design Research Institute (DRI) at the RMIT University in Melbourne hosted a Design Challenge on ageing. For the institute, which is based around trans‐disciplinary design research, the challenge provides a unique opportunity to introduce a rigorous framework and focus to its activities. Katherine Wilkinson, the Senior Manager of the DRI and initiator of the annual Design Challenge, describes how students, designers and experts from industry, business and the community were brought together by the issue of ageing to generate innovative ideas and solutions.